A comprehensive contingency management framework for supply chain disruption risk management. (2015) - Zhang, Yibin; Long, Jing; Shi, Chunming
With globalisation and the advancement of information and communication technology, supply chain network structure has become more and more complicated with operational uncertainties and disruptions increasingly exacerbated. In this paper, we propose a comprehensive emergency management framework to manage supply chain disruption risks. Our framework integrates risk identification, risk assessment, and a combination of two contingency strategies. These two strategies are robust inventory control and virtual dual sourcing which can effectively mitigate supply chain disruptions. We then present a case study where Delphi Co. managed the disruptions in its supply chains during the 2008 Olympic Games in Beijing, China. Through this case study, we show the validity of our comprehensive emergency management framework. Finally, our framework can improve supply chain sustainability. For example, its strategy of virtual dual sourcing can keep a supply chain sufficiently lean while minimising the effect of supplier disruption.